Impacts of linkage risks on the sustainable development of agricultural tourism value chains: Evidence from the North Central region of Vietnam - Nguyen, Thi Bich Thuy; Tran, Quang Bach; Nguyen, Thi Thu Cuc; Ho, Thi Dieu Anh; Duong, Thi Quynh Liên; Hoang, Thi Viet (Edelweiss Applied Science and Technology, 2025)
In the current context, the development of agricultural tourism with its diverse activities has gradually become a global trend. This study aims to examine the relationships between linkage risks and the sustainable development of agricultural tourism value chains in the North Central region of Vietnam. A quantitative research method was employed through structural equation modeling (SEM). Research data were collected from a survey of 471 participants involved in the agricultural tourism value chain, including tourism companies and agricultural organizations. The findings reveal that among the identified risk factors, only supply-side risks and customer-related risks exert direct and negative impacts on the sustainable development of agricultural tourism value chains. Meanwhile, linkage integration plays a mediating role in the relationships between information risks, environmental risks, and sustainable development of agricultural tourism value chains. These results highlight the valuable contributions of the study and provide a foundation for future research. Based on the findings, several recommendations are proposed to foster the sustainable development of agricultural tourism value chains in the North Central region of Vietnam.